タンショク コウ サツゾウ システム ニ ヨル オーロラ カンソク ト データ ショリ - 小野, 高幸; オノ, タカユキ; 江尻, 全機; エジリ, マサキ; 平澤, 威男; ヒラサワ, タケオ; Ono, Takayuki; Ejiri, Masaki; Hirasawa, Takeo (1988)
P(論文) 昭和基地におけるJARE-25オーロラ観測では, 新たな試みとして単色光オーロラ撮像を行うテレビカメラシステムが導入され, 地上における超高層モニタリング観測, ロケット観測, 人工衛星観測および共役点オーロラの同時観測に使用された。本システムは, イメージ増倍管とCCDを用いた新世代のテレビカメラであり, またディジタルデータとして収録される特徴を持っている。この特徴を生かしたデータ再生, ならびに画像解析用ソフトウェア体系が国立極地研究所大型電算機を用いて開発された。この報告ではテレビカメラシステムの概要, ならびにデータ処理用ソフトウェアについて述べ, さらにこれまでに明らかになった主たる結果についてふれる。 A new TV camera was developed and applied to the auroral ovservation at Syowa Station, Antarctica, in 1984. The TV camera is to obtain monochromatic auroral images at the principal auroral emission lines such as 6300Å (OI), 5577Å (OI), 4861Å (Hβ) and 4278Å (1N N_2^+), and band (6000～8000Å; 1P N_2). An important merit of the new TV camera is digital recording of the observation data. Successive monochromatic auroral images transferred from the TV camera every few seconds are digitized and converted to digital data stream simultaneously and recorded by a high speed data recorder in a PCM format. Observations by using three sets of the TV cameras were carried out throughout the winter season in 1984 at Syowa Station by JARE-25 wintering party. The TV cameras were used also for cooperations with (i) sounding rocket experiments, (ii) auroral particles, plasma and plasma wave experiments on board the EXOS-C satellite and (iii) conjugate auroral observation campaign which was carried out in lceland. The data processing software system was established by using a host computer in the National Institute of Polar Research. We developed the data reproduction software to convert the PCM data to the computer compatible digital data. The data can be monitored by a display software which is also able to make a coordinate transform from the original TV image to an ionospheric geomagnetic coordinate system. By using this method, we found that a diffuse auroral band which is located equatorward of an oval of discreate auroras, corresponds to the proton auroral band in the evening sector. For a special purpose to analyze the pulsating auroral phenomena, we developed an autocorrelation analyses software which gives a ...